Computer Knowledge and Anxiety in Student Learning Outcome: The Role of Learning Motivation as Mediator - Nafra Mutya Weti; Muhammad Fahmi Johan Syah (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The research is being carried out among the students of the SMK Accounting and Finance Institute who are still not mastered in computer knowledge, have anxiety about the use of computers, and lack motivation towards learning outcomes. This study aims to examine the role of learning motivation as a mediator between computer knowledge and computer anxiety in student learning outcomes. This type of research is quantitative with a path analysis correlation design. The number of respondents in this study was 90 students of SMK Negeri 1 Boyolali. The results showed that the learning motivation variable is a mediator variable between computer knowledge and learning outcomes. However, the results of the analysis also show that the learning motivation variable is a mediator variable between computer anxiety and learning outcomes, while computer knowledge and computer anxiety have an effect but are not significant on learning outcomes. Therefore, to improve learning outcomes through increasing students' computer knowledge, learning motivation is needed. Meanwhile, increasing computer anxiety decreases motivation and learning outcomes, but not significantly. Therefore, learning motivation has an important role in mediating computer knowledge and computer anxiety on student learning outcomes in spreadsheet subjects for accounting. Further research is expected to find out what other factors affect student learning outcomes in accounting spreadsheet subjects.